Islamic leadership principles at IIUM - Mohd. Israil, Khaliq Ahmad; Fontaine, Rodrigue Ancelot Harvey (KENMS-IIUM Press, 2011)
This paper is an empirical study related to Islamic leadership. Our literature review focuses on transactional leadership, transformational leadership and servant leadership. The literature suggests that Islamic leadership most closely resembles servant leadership. We then used a questionnaire to assess how administrators at the International Islamic University Malaysia (IIUM) view the leadership approaches of their direct superiors and which leadership approach they prefer. The results of the survey clearly indicate that they prefer servant leadership followed by transformational leadership. Respondents dislike transactional leadership. The implications of the studies are discussed and the possibility of generalisation is discussed.